Pengembangan media pembelajaran Ilmu Sosial Budaya berbasis Kearifan Lokal (Kain Sasirangan khas Kalimantan) - Normalasarie Normalasarie; Siti Aulia (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
this study is aimed to produce local wisdom based teaching media and to introduce Kalimantan’s unique garment. The objective of this study is constructs a teaching media to preserve endangered cultural items in Kalimantan. This study is carried under a model proposed by William W Lee and Diana L Owens (2004) which consists of 5 (five) stages. First, assessment analysis stage which is divided into need assessment and front -end analysis. This stage reveals complete information on kinds of media to be developed. Second, design stage where the blueprint and the production schedule of the media are made. Third is the development stage where the design is transformed into physical form. Fourth, the implementation stage contains expert validation of the media. Fifth stage is the evaluation of the media. The instrument applied in this study is questionnaire. The data then analyzed on three steps of analysis, field test, limited scale test, and operational product test. The result of this study reveals that the use of the media is recommended since it enhances the ability, the interest, and the achievement of students thus it is also appropriate for PPL students to be used on their apprenticeship period.